Excited state properties of 5-formylcytosine and 5-hydroxymethylcytosine. (17th November 2017) - Mato, Joani; Keipert, Kristopher; Gordon, Mark S.
ABSTRACT: Excited state properties are investigated for two natural analogues of cytosine, 5-hydroxymethylcytosine (5hmC) and 5-formylcytosine (5fC). Excited state calculations using multi-reference perturbation theory (MR-MP2), equations of motion singles and doubles coupled cluster theory and time-dependent density functional theory within the Tamm–Dancoff approximation show that 5fC differs from cytosine in that the dark nπ* state localised on the formyl group is lower in energy than the bright ππ* state. The singlet state ordering for 5hmC, on the other hand, matches that of cytosine, with the bright ππ* state located lower in energy than the nπ* state. The potential energy surface of 5hmC was also examined. Upon excitation of 5hmC to the bright ππ* state, MR-MP2 calculations show that the most likely decay mechanism involves the ππ* state with a 0.27 eV barrier leading to a conical intersection with the ground state. The present calculations suggest that the nπ* state is unlikely to contribute to the decay mechanism of 5hmC. Abstract :